New record of white-spotted pufferfish Arothron hispidus (Linnaeus, 1758) (Tetraodontiformes: Tetraodontidae) from West Bengal, India, compared with other Arothron species occurring in India - Mishra, Subhrendu Sekhar; Chakraborty, Priyankar; Yardi, Kranti (Journal of Fisheries, 2021)
Two specimens of Arothron hispidus (Linnaeus, 1758) (111.7 – 112.8 mm in standard length), was collected in May 2019 from the Frasergunj fishing harbour in West Bengal, eastern India. Herein, we report this species for the first time from West Bengal. We have described the diagnostic features of the collected specimens and compared them with other Arothron species found in Indian waters.